A comparison of the acute effects of calcium and strontium ranelate on the serum marker of bone resorption - Maresova, Kristyna Brabnikova; Franek, Tomas; Vondracek, Tomas; Stepan, Jan J (Clinical chemistry and laboratory medicine, 2011)
BACKGROUND: To investigate the mechanism by which strontium ranelate (SrR) inhibits the bone resorption, this study compared the effects of SrR and calcium on parathyroid hormone (PTH) and the biochemical marker of bone resorption (serum type 1 collagen cross-linked C-telopeptide, βCTX). METHODS: In 10 healthy young subjects, after overnight fasting, 1000 mg of elemental calcium and 2000 mg of SrR containing 600 mg Sr²⁺ were administered consecutively with a 1 week washout period. During the control period no drug was given. Fasting blood samples were drawn at baseline and throughout the next 5-h period. RESULTS: After the ingestion of either calcium or SrR, there was a significant increase in serum calcium and strontium concentrations, and a decrease in serum βCTX and intact PTH concentrations as compared to the baseline values (p<0.05). In the fasting subjects, no significant differences in the variable were found as compared to the baseline values. CONCLUSIONS: The decrease in PTH and the marker of bone resorption observed after the SrR administration is comparable to the decrease observed after the calcium administration in young adults.
Keywords: Calcium; Fasting; resorpce kosti; Humans; referenční standardy; kolagen typu I; regulace genové exprese; Thiophenes; vápník; Female; mladý dospělý; dospělí; Collagen Type I; Administration, Oral; lidé; Biomarkers; Organometallic Compounds; peptidy; Parathyroid Hormone; Reference Standards; organokovové sloučeniny; Peptides; Adult; biologické markery; ženské pohlaví; Gene Expression Regulation; Male; parathormon; Young Adult; omezení příjmu potravy; Bone Resorption; aplikace orální; thiofeny; mužské pohlaví